VISIONS remote observations of a spatially-structured filamentary source of energetic neutral atoms near the polar cap boundary during an auroral substorm. Issue 10 (15th November 2015) - Collier, Michael R.; Chornay, D.; Clemmons, J.; Keller, J.W.; Klenzing, J.; Kujawski, J.; McLain, J.; Pfaff, R.; Rowland, D.; Zettergren, M.
Abstract: We report initial results from the VISualizing Ion Outflow via Neutral atom imaging during a Substorm (VISIONS) rocket that flew through and near several regions of enhanced auroral activity and also sensed regions of ion outflow both remotely and directly. The observed neutral atom fluxes were largest at the lower energies and generally higher in the auroral zone than in the polar cap. In this paper, we focus on data from the latter half of the VISIONS trajectory when the rocket traversed the polar cap region. During this period, many of the energetic neutral atom spectra show a peak at 100 eV. Spectra with peaks around 100 eV are also observed in the Electrostatic Ion Analyzer (EIA) data consistent with these ions comprising the source population for the energetic neutral atoms. The EIA observations of this low energy population extend only over a few tens of km. Furthermore, the directionality of the arriving energetic neutral atoms is consistent with either this spatially localized source of energetic ions extending from as low as about 300 km up to above 600 km or a larger source of energetic ions to the southwest.